The pumpkin cookbook : 139 recipes celebrating the versatility of pumpkin and other winter squash - Stovel, Edith, 1940- (Storey Publishing, 2017)
Pumpkin is a versatile and healthy option for every meal of the day. DeeDee Stovel's creative recipes highlight the preparation techniques and many forms - including raw, roasted, canned, and steamed.